Literature Study on Coal Acid Mine Drainage Management Using Phytoremediation Method - Simamora, Eprilia; Nurcholis, Mohammad; Adrian, ⁠Aldin; Ernawati, Rika; Winarno, Eddy (Inovbook Publications, 2024)
Literature study on the management of Acid Mine Drainage through phytoremediation has become crucial to gain a better understanding of its potential, challenges, and recent developments. The research method employed in this study is Literature Review. Literature Review involves a series of activities related to collecting literature data, reading and note-taking, as well as processing research materials. The findings reveal that using a greater variety of plants provides a more comprehensive overview. The use of diverse plants or more complex phytoremediation systems offers a broader understanding. The evaluation of plant abilities in absorbing iron (Fe) and manganese (Mn) is emphasized. Adding evaluations for other metals or potential pollutants would enhance the research completeness. A decline in plant absorption abilities after ten days is observed, but external factors such as temperature, pH, or environmental conditions affecting this decline are not extensively discussed